2011
DOI: 10.1016/j.socscimed.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Culture, gender and health care stigma: Practitioners’ response to facial masking experienced by people with Parkinson’s disease

Abstract: Facial masking in Parkinson’s disease is the reduction of automatic and controlled expressive movement of facial musculature, creating an appearance of apathy, social disengagement or compromised cognitive status. Research in western cultures demonstrates that practitioners form negatively biased impressions associated with patient masking. Socio-cultural norms about facial expressivity vary according to culture and gender, yet little research has studied the effect of these factors on practitioners’ responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 62 publications
4
69
0
1
Order By: Relevance
“…A number of studies have shown that practitioners form inaccurate and negatively biased impressions of patients' personalities (relative to patients' self-reports) (Lyons, Tickle-Degnen, Henry, & Cohn, 2004;Tickle-Degnen, Zebrowitz & Ma, 2011). Compared to rehabilitation professionals, rehabilitation students were particularly likely to rate patients with high levels of masking as less extraverted .…”
Section: Impressions Of People With Expressive Disordersmentioning
confidence: 99%
“…A number of studies have shown that practitioners form inaccurate and negatively biased impressions of patients' personalities (relative to patients' self-reports) (Lyons, Tickle-Degnen, Henry, & Cohn, 2004;Tickle-Degnen, Zebrowitz & Ma, 2011). Compared to rehabilitation professionals, rehabilitation students were particularly likely to rate patients with high levels of masking as less extraverted .…”
Section: Impressions Of People With Expressive Disordersmentioning
confidence: 99%
“…The frozen position of pressed or slack lips and an unbroken stare creates the impression, regardless of its accuracy, of an asocial, cold, incompetent or apathetic person who fails to reciprocate others' feelings of warmth, concern, interest or excitement [9]. The mask interferes with social observers' formation of accurate impressions regardless of whether the observer is a layperson or a health care practitioner [15,35]. The experience for people with masking is an imprisonment of the self in an unresponsive face and body [3], feeling misunderstood, isolated and lonely [32].…”
Section: The Problem: Caregiver-patient Stigmatizationmentioning
confidence: 99%
“…This indecipherability sets the stage for social response biases and stereotype activation as the social observer attempts to understand an ambiguous situation. The lack of predictability and the reduced perceived trustworthiness of the facially masked patient in comparison to more expressive patients may explain why observers have negative responses to facial masking [35]. People who are more expressive are liked more and viewed as more trustworthy than are less expressive individuals [8].…”
Section: The Problem: Caregiver-patient Stigmatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from affecting the facial expressivity of individuals with PD, hypomimia may color how others perceive these individuals (Monrad-Krohn, 1957;Tickle-Degnen, Zebrowitz, & Ma, 2011). After viewing the silent videorecordings of PD participants, raters judged them to be more anxious.…”
Section: Introductionmentioning
confidence: 99%